2013
DOI: 10.1080/00071668.2013.771392
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcase and meat traits and gene expression in chickens divergently selected for intramuscular fat content

Abstract: 1. Changes resulting from divergent selection after 5 generations for intramuscular fat (IMF) content in breast muscle in a population of purebred Beijing-You chickens were investigated. Female chickens from lines selected-up (UL) and selected-down (DL) for 5 generations and random-bred controls (CL) were studied at 120 d of age. 2. In the UL, IMF in breast muscle (4.65%) was 1.38 times that in the DL (3.36%). The IMF content in leg muscle was also higher in UL compared to DL. 3. There were significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This approach identified the gene set that best correlates to IMF% is triacylglyceride (TAG) deposition, and includes FABP4. A number of other groups have identified similar sets of genes in various production species based on similar analyses performed on similar experimental designs (Saez et al, 2009;Li et al, 2013;Wang et al, 2013;Ren et al, 2014). However, to date the simplest measures of DE and correlations of abundance to phenotype have yielded only modest regulatory insight.…”
Section: Introductionmentioning
confidence: 99%
“…This approach identified the gene set that best correlates to IMF% is triacylglyceride (TAG) deposition, and includes FABP4. A number of other groups have identified similar sets of genes in various production species based on similar analyses performed on similar experimental designs (Saez et al, 2009;Li et al, 2013;Wang et al, 2013;Ren et al, 2014). However, to date the simplest measures of DE and correlations of abundance to phenotype have yielded only modest regulatory insight.…”
Section: Introductionmentioning
confidence: 99%
“…Broiler breeders have given attention to abdominal fat to improve both meat quality and efficiency of feed conversion (Li et al . ). Previous studies showed that there were no significant differences of IMFC in leg muscle (Ricard et al .…”
Section: Introductionmentioning
confidence: 97%
“…This includes fatty acid synthase (FASN) which was found to correlate with meat weight loss during the first salting of dry-cured ham production [143], meat quality including marbling in cattle [144] and playing a role in the mammary gland and milk in goats and cattle [145,146], in addition to many other roles. Differing H-FABP polymorphisms/expression levels have also been related to growth rate and size of beef cattle and chickens and could therefore provide useful markers for breeding [147,148].…”
Section: Future Faty Acid Research and Medicinementioning
confidence: 99%